Experimental Study on the Effect of Emergency Braking without Anti-Lock Braking System to Vehicle Dynamics Behaviour - I. M., Zulhilmi; Mohamad Heerwan, Peeie; S. M., Asyraf; I. M., Sollehudin; I. M., Ishak (Universiti Malaysia Pahang, 2020)
An anti-lock braking system (ABS) is a basic skid control system that can prevent the tire from locking up. In an emergency braking situation, a high possibility that the skidding phenomenon can occur without ABS. This incident become worse when an emergency braking is applied either on wet or dry surfaces. Although ABS is crucial to prevent the collision, some vehicles still do not have ABS. This study is aimed to analyse the vehicle’s dynamic behaviour during emergency braking on wet and dry surface condition. The experimental vehicle model is a Malaysian sedan car namely Proton Persona. This instrumented car is equipped with sensors, video camera and data acquisition systems to determine the vehicle’s motion. In the experiment, when the vehicle reached a maximum speed of 60 km/h, the driver push the brake pedal firmly until the car stop. From the experimental results, the effect of emergency braking without ABS is clearly seen at the wheel speed. The tire locked up can be observed when emergency braking was applied on the wet surface. However, for the emergency braking on the dry surface, the tire decreased gradually. This finding shows that without ABS, the vehicle is unsafe and accident can occur. The experimental data from this study also can be used as a guideline to a researcher and manufacturer in the development of ABS and safety system of the vehicle